Optimizing the potential of vinasse as additive electrolyte for sulfuric acid in lead acid batteries using mixture D-optimal design. - Gascon, Grand C.
Vinasse, the dark brown byproduct of distillation, continuously threatens the environment in a negative manner, especially with the increase of ethanol demand. Aiming to increase Vinasse consumption, this study optimized the potential of Vinasse as additive electrolyte for Sulfuric acid (H2SO4) in a 2 V Lead acid battery system by looking at its Charge Cycle, Discharge Cycle, and Battery Efficiency using Mixture D-Optimal Design. Thirty minutes of charging and thirty minutes of discharging cycles were performed in a 33% Dilute H2SO4 Control Variable Electrolyte, before repeating the same charge and discharge cycles to 13 varying ratios of Vinasse + H2SO4 electrolyte that was generated by Mixture D-Optimal Design. It was discovered that the optimum ratio was 67.476% Vinasse and 32.524% H2SO4. The Total Charged Voltage after 30 minutes of charging the 33% Dilute H2SO4 Electrolyte was 0.3167V, while the Total Charged Voltage of the Optimum Vinasse + H2SO4 electrolyte was 0.1467V. The Total Discharged Voltage of the 33% Dilute H2SO4 Electrolyte was 0.11V, while the Optimum Vinasse + H2SO4 electrolyte only had 0.0433V, indicating that the Vinasse + H2SO4 Electrolyte performed better in the Discharge Cycle. The Battery efficiency obtained for the dilute H2SO4 electrolyte was 85.08%, while the Battery Efficiency of the Optimum Vinasse + H2SO4 electrolyte was 84.10%. The Optimum Vinasse + H2SO4 electrolyte was then spiked with Phosphates and Nitrates, and it was determined that these two impurities did not have a significant effect on the overall Battery Efficiency of the Lead acid battery. This experiment is evident that the addition of Vinasse as additive in a lead acid battery could offer a lesser discharged Voltage over time.